Eu, tu e ele (a) - Diálogo ecumênico em São José dos Campos: Avanços, dificuldades, caminhos, perspectivas - Mortl, Maria Inez de Lima (2005)
The Christian churches, mainly the historical ones have, in the ecumenical dialog, the opportunity to live their faith, and to profess, in a non pre-conceptual manner, without proselytism and with the conviction that the God revelation as Trinity (Father, Son and Holy Ghost) is not restrict to any church exclusively. The theme ecumenism remains vital nowadays due to the cultural and religious plurality present in our society. The investigation s object of this work is the Movimento Ecumênico do Município (MEM) of São José dos Campos SP Vale do Paraíba region. Be part of this movement mainly the historical Christian churches, but are also present the Pentecostal and even the Neo-Pentecostal churches. This research had the objective to study the MEM in the period from 1999 to 2001, between clergy and laymen of the historical churches, focusing on the advances, difficulties, directions and the perspectives from this movement. In this analysis, I detected three ecumenical dialog models: theological-doctrinal ecumenism, institutional celebrative ecumenism and practical ecumenism. The work proposes to find possible solutions for the advances on the ecumenical dialog. The hypothesis is that maybe there is a deficiency of this advance on the ecumenical dialog due to the lack of a common ideal, i.e., lack of a united social action, which would characterize the Christians as authentic. The theoretical structure was based on studies of protestant and catholic theologians who approach the inter-clerical dialog, as well as information and positions from many churches and ecumenical organisms. For the churches historic that belong to MEM, as well as to discover their real difficulties, was accomplished interviews and research in the churches and municipal registry offices. The research, done under a scientific vision, can favor the comprehension that the true ecumenism begins through a concrete action, or, in other words, through practicing the Gospel. This process can lead the ecumenical movement to achieve its objective: the unity on the diversity for the world to believe . Therefore, it leads to the expansion of MEM in the region that belongs to and also its results can be projected in the environments on which is proposed this unity on the diversity